Ending hunger by 2030 - actions and costs - von Braun, Joachim; Chichaibelu, Bezawit Beyene; Torero, Maximo; Laborde Debucquet, David; Smaller, Carin (United Nations Food Systems Summit, 2021)
The 2030 Agenda for Sustainable Development pledged to move away from growing inequality to more inclusive, shared growth, away from ecocide, mass extinction of our plant and animal biodiversity, and waste and destruction of our planet’s abundant but still finite natural resources to practices that respect and protect our common home, and away from activities that expose hundreds of millions of people to the insidious effects of rising global temperatures and its consequences for climate risks. At the heart of the 2030 Agenda was a promise to prioritize to eradicate poverty and end hunger and malnutrition in all their forms.